Odissi - Lowen, Sharon; Pasricha, Avinash (New Delhi : Wisdom Tree, 2004)
In this book, the actual practitioners of Oddissi dance forms, the dancers themselves, give the insider's point of view, the origin and history, the music, the costumes, make-up and specific jewellery
Keywords: Dance -- Orissa -- India; Odissi dance -- Orissa -- India; Odissi dance -- Orissa -- India -- Origin; Odissi dance -- Orissa -- India -- Equipment and supplies